Cyclofenil as a possible cause of non-arteritic anterior ischaemic optic neuropathy. (20th December 2012) - Clarke, Benjamin; Sykakis, Evripidis; Parmar, Dipak N
Abstract : A 27-year-old woman receiving the steroid drug cyclofenil as a fertility adjunct, experienced blurred vision 24 h after missing a dose and taking a double dose to 'catch up' with her therapeutic protocol. She was found to have a non-arteritic anterior ischaemic optic neuropathy with a visual hemifield defect and impaired optic nerve function, which has not since shown any recovery. This case highlights the prothrombotic potential for the drug when used above normal dosing range, and is therefore of great guidance for those initiating it as a fertility treatment, or in unlicensed use.